Determination of genetic divergence among castor bean accesses by using binary and multicategorical characters - Rodrigues, Helen Cristina de Arruda; Carvalho, Samuel Pereira de; Carvalho, Alexandre Alves de (Revista de Ciências Agroveterinárias, 2015)
The objective of this work was to characterize morphologically and to evaluate the genetic diversity between fifteen groups of castor bean (Ricinus communis). The experiment was conducted in a randomized blocks design with fifteen treatments and three replications and was carried out in dystroferric Red Latosol in Lavras, MG, Brazil. Data was submitted to variance analysis, getting the genetic distances between the groups and on the basis of these distances, based on multivariate analysis, the genetic divergence was determined by using cluster analysis and principal components analysis. Three groups were formed, so that it was evidenced genetic divergence in the dissimilarity matrix. Group I formed by twelve genotypes, group II formed by two genotype and group III formed by one genotype, access nine. The use of multicategorical characters was efficient for the determination of genetic divergence among castor beans.